Anaesthetic management in the excision of large carotid body tumours: Surgeons perspectives - Serina Ruth Salins; Prabhu Prem Kumar; Edwin Stephen; Deepak Selvaraj (International Journal of Medical Research and Review, 2016)
Objective(s): Carotid body tumours (CBT) are considered rare. Surgical excision is the treatment of choice and poses many anaesthetic challenges especially in large tumours. In this paper we present our experience of anaesthetic management of CBT which is one of the largest series on management of large (Shamblin II, III) tumours in the world.Design: Retrospective cohort, Instituitional Review Board (IRB) Approved.Setting: Single-Centre Tertiary care institute in South India.Participants: Patients undergoing operative intervention for carotid body tumours.Interventions: nil, observational.Results: 66 tumours were excised in 62 patients (27 female, 39 male). The average age was 37.5. All tumours presented with a slow growing neck mass.7 patients complained of pain,as the presenting symptom. 2 were malignant, all were non-functional. 4 presented with preoperative neurological dysfunction- 2 with cranial nerve palsy following excision of contralateral CBT and 2 with resolved stroke following preoperative embolization. Nasotracheal intubation with mandibular subluxation was performed in 5. The average operating time was 2.5 hours. Average blood loss was 900 ml (200- 5000ml). Perioperative blood or product requirement varied from no transfusion to one patient with a very large (20cm tumour) requiring transfusion of a total of 20 products. Clamping of the carotid was necessary in 22 patients. 3 patients received heparin prior to clamp. There were 4 perioperative strokes, none of whom had any precipitous intraoperative hypotension. Transient postoperative cranial nerve palsy/paresis occurred in 50% with permanent cranial nerve deficits in 5%. There was no perioperative mortality. Tracheostomy was required in one patient for bilateral vocal cord palsy.Conclusions: Several preoperative, intraoperative and postoperative management points (airway, intraoperative blood loss, stroke, cranial nerve dysfunction ,blood pressure control), are specific to the management of carotid body F tumours.Increased awareness of these specific scenarios and appropriate management ensures minimal perioperative morbidity and mortality.